Development of Self-Efficacy in Clinical Communication Skills in a Student-Run Free Clinic - Emily Floramo; Joseph Rumenapp; Izhani Rosa; Melissa Chen; Meredith Baker-Rush (Journal of Student-Run Clinics, 2024)
Background: Student Run Free Clinics (SRFCs) provide early opportunities for health professions students to engage in clinical learning and develop professional skills. They also provide a supportive learning space for students to develop self-efficacy (SE). However, little is known regarding whether SRFCs provide opportunities for students to develop SE in clinical communication skills.   Methods: A survey containing 24 items about SE in clinical communication on a 10-point attitude scale and 4 open-ended items was distributed to all students at a health professions university. A Mann-Whitney test was used to compare quantitative responses of participants who volunteered in an SRFC and those who did not. A thematic qualitative analysis was conducted on the open-ended responses. Finally, the qualitative and quantitative analysis was considered together to better understand the development of SE in an SRFC.Results: A total of 27 students across 6 professional programs participated in the survey. There was no significant difference in SE of communication skills between SRFC student volunteers and non-SRFC students (U=77.5, p=0.71). In the qualitative analysis, SRFC student volunteers seemed to differentiate the SRFC from other clinical experiences while non-SRFC students anticipated that SRFC service could lead to more clinical practice in a safe learning environment.Conclusions: Our results demonstrate that SE in clinical communication skills of SRFC student volunteers may not differ from non-SRFC students. However, the perceived benefits from participating and learning in a SRFC was found to have a positive impact. SRFCs may provide a special and safe space for student learning while also providing opportunities to practice clinical communication. Additionally, explicit focus on developing clinical communication skills in SRFCs may further help students with developing SE.